2017
DOI: 10.1021/acsnano.7b06295
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Thermal Regulation Textiles

Abstract: Space cooling is a predominant part of energy consumption in people's daily life. Although cooling the whole building is an effective way to provide personal comfort in hot weather, it is energy-consuming and high-cost. Personal cooling technology, being able to provide personal thermal comfort by directing local heat to the thermally regulated environment, has been regarded as one of the most promising technologies for cooling energy and cost savings. Here, we demonstrate a personal thermal regulated textile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
275
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(278 citation statements)
references
References 51 publications
0
275
0
3
Order By: Relevance
“…[98,99] For practical application, the manufacturing process of wearable sensors should be cost-effective, scalable, capable of large area, and easy production. Park et al [101] have dip coated a fabric yarn to CuZr alloy (metallic glass)/PDMS Co-sputtering [12] Silver nanowire (Ag NW)/PDMS Vacuum filtration transfer [18] Silicone prepolymer/Al Spin coating [19] Ag-NW/styrene-butadiene-styrene (SBS) Solution casting [44] Ag-NW/cotton Dip coating [49] Silica NP/PDMS/cellulose acetate/IL/silver/cotton Coating/thermal evaporation [50] Aligned boron nitride (BN)/polyvinyl alcohol (PVA) 3D printing [51] PEDOT/cloth Coating/vapor phase polymerization [52] Nylon-6 nanofiber/Ag/nanoporous polyethylene (nano-PE) Electrospinning/electroless plating [53] Graphene/polyisobutylene (PIB)/PDMS Chemical vapor deposition/spin coating [54] Copper nanowire (Cu-NW)/poly (methyl methacrylate) (PMMA) Spray coating/spin coating [55] Cu wire/alumina/polyimide/PDMS Atomic layer deposition (ALD)/spin coating [178] Actuator/muscle MWCNT/carbon nanofiber/PEDOT:PSS Electrospinning/drop casting [6] Graphene oxide/vapor grown carbon fiber (VGCF)/IL Solution casting [8] PEDOT:PSS Wet spinning/ chemical treatment [17] Bacterial cellulose (BC)/IL/graphene Solution casting [23] PEDOT:PSS/VGCF/IL Solution casting [33] IL/polyurethane/PEDOT:PSS Solution casting [34] BC/IL/ionic polymer Dip coating [59] PEDOT-polystyrene sulfonic acid (PEDOT:PSS)/IL/BC Solution casting [179] Poly(ionic liquid)(PIL)/polyacrylic acid/paper Dip coating [65] Drug delivery Mesoporous silica nanoparticle Transfer printing [21] PDMS Soft lithography [61] www.advmat.de www.advancedsciencenews.com form a highly stretchable strain sensor that can stretch up to 150% along its axis while Lipomi et al [102] spray coated CNT to form a stretchable strain sensor. [100][101][102]…”
Section: Materials Structures and Methods In Wearable Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[98,99] For practical application, the manufacturing process of wearable sensors should be cost-effective, scalable, capable of large area, and easy production. Park et al [101] have dip coated a fabric yarn to CuZr alloy (metallic glass)/PDMS Co-sputtering [12] Silver nanowire (Ag NW)/PDMS Vacuum filtration transfer [18] Silicone prepolymer/Al Spin coating [19] Ag-NW/styrene-butadiene-styrene (SBS) Solution casting [44] Ag-NW/cotton Dip coating [49] Silica NP/PDMS/cellulose acetate/IL/silver/cotton Coating/thermal evaporation [50] Aligned boron nitride (BN)/polyvinyl alcohol (PVA) 3D printing [51] PEDOT/cloth Coating/vapor phase polymerization [52] Nylon-6 nanofiber/Ag/nanoporous polyethylene (nano-PE) Electrospinning/electroless plating [53] Graphene/polyisobutylene (PIB)/PDMS Chemical vapor deposition/spin coating [54] Copper nanowire (Cu-NW)/poly (methyl methacrylate) (PMMA) Spray coating/spin coating [55] Cu wire/alumina/polyimide/PDMS Atomic layer deposition (ALD)/spin coating [178] Actuator/muscle MWCNT/carbon nanofiber/PEDOT:PSS Electrospinning/drop casting [6] Graphene oxide/vapor grown carbon fiber (VGCF)/IL Solution casting [8] PEDOT:PSS Wet spinning/ chemical treatment [17] Bacterial cellulose (BC)/IL/graphene Solution casting [23] PEDOT:PSS/VGCF/IL Solution casting [33] IL/polyurethane/PEDOT:PSS Solution casting [34] BC/IL/ionic polymer Dip coating [59] PEDOT-polystyrene sulfonic acid (PEDOT:PSS)/IL/BC Solution casting [179] Poly(ionic liquid)(PIL)/polyacrylic acid/paper Dip coating [65] Drug delivery Mesoporous silica nanoparticle Transfer printing [21] PDMS Soft lithography [61] www.advmat.de www.advancedsciencenews.com form a highly stretchable strain sensor that can stretch up to 150% along its axis while Lipomi et al [102] spray coated CNT to form a stretchable strain sensor. [100][101][102]…”
Section: Materials Structures and Methods In Wearable Sensorsmentioning
confidence: 99%
“…The presented breathable and washable cloth has claimed more than 30 times energy savings per person when compared with the traditional building heating based approach. Gao et al [51] have prepared thermally conductive polymer based fiber and have incorporated it into a fabric to enhance the thermal conductivity. Multifunctional and hydrophobic cloth presented by Liu et al [50] has used infrared (IR) reflective properties of silica nanoparticle composite to prevent heat loss from the user to keep them warm during winter seasons ( Figure 2b).…”
Section: Wearable Heating Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gao et al [97] 3D-printed (shown in Figure 8) boron nitride (BN)/poly(vinyl alcohol) (PVA) conductive composite fibers for efficient personal cooling with thermal regulation textiles. The highly aligned printed BN nanosheets in the microfibers performed heat transfer efficiently with the surrounding medium.…”
Section: Stretchable and Flexible Interconnects And Conductive Textilesmentioning
confidence: 99%
“…h) Schematic illustration of the thermal regulation textile [40]. a) Schematic of the fabrication process of a-BN/PVA composite fiber.…”
mentioning
confidence: 99%